2017
DOI: 10.7883/yoken.jjid.2015.658
|View full text |Cite
|
Sign up to set email alerts
|

The Phantom Menace for Patients with Hepatobiliary Diseases: <i>Shewanella haliotis</i>, Often Misidentified as <i>Shewanella algae</i> in Biochemical Tests and MALDI-TOF Analysis

Abstract: SUMMARY: Although Shewanella algae has been known to have weak pathogenicity, case reports on infections with this species have been steadily increasing. S. algae and S. haliotis are difficult to distinguish from each other with conventional phenotypic methods. We reviewed the microbiological and clinical features of S. algae and S. haliotis infections at our institute. Bacterial culture and identification reports from patient samples from 2010 to 2014 were reviewed to screen the cases of Shewanella infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…State-of-the-art methods can discriminate between S. algae and S. putrefaciens on the basis of their biochemical and phenotypic characteristics [ 1 ]. Similar tests have been reported, though, to be inconclusive for discrimination of S. algae from other emerging pathogenic Shewanella , thereby requiring molecular techniques that include 16S rRNA and/or gyrB DNA sequencing for accurate species identification [ 39, 40 ]. Byun et al .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…State-of-the-art methods can discriminate between S. algae and S. putrefaciens on the basis of their biochemical and phenotypic characteristics [ 1 ]. Similar tests have been reported, though, to be inconclusive for discrimination of S. algae from other emerging pathogenic Shewanella , thereby requiring molecular techniques that include 16S rRNA and/or gyrB DNA sequencing for accurate species identification [ 39, 40 ]. Byun et al .…”
Section: Discussionmentioning
confidence: 78%
“…Byun et al . reported the inability to discriminate between S. algae and S. haliotis on the basis of biochemical and phenotypic assays [ 39 ]. Even 16S rRNA sequencing, not routinely conducted in the clinical microbiology laboratory, can be insufficient to determine the identity of an isolate at the species level (E. Fernández-Fernández et al ., unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…was only detected in fish showing clinical signs of a disease, namely S. algae and S. seohaensis . Reports on infections of human patients with S. algae , S. haliotis , S. putrefaciens and S. xiamenensis are published, and in these reports, the detection of S. algae exceeded those of S. putrefaciens (Byun, Park, & Kim, ). One reason for a higher virulence of S. algae might be the possible production of tetrodotoxin by this species (Simidu, Kita‐Tsukamoto, Yasumoto, & Yotsu, ; Simidu, Noguchi, Hwang, Shida, & Hashimoto, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, Shewanella -associated infections have been reported in Thailand [1], Japan [26] and Taiwan [11] of China. Risk factors of human infections attributed to the genus Shewanella occur in warmer climates.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective investigation of Shewanella bacteremia in patients with hepatobiliary disease from Taiwan, China indicated that, five out of nine Shewanella strains were confirmed as the S. haliotis using 16S rRNA sequencing analysis [11]. Byun JH et al [26] reported 19 strains which were identified as S. algae by using VITEK 2 and Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry, whereas 16S rRNA analysis identified 10 isolates as S. algae and 9 isolates as S. haliotis . The reason is that only two Shewanella species, S. putrefaciens and S. algae were registered in the database of VITEK 2 system and MALDI-TOF mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%